MRI‐guided targeted needle placement during motion using hydrostatic actuators. Issue 2 (19th January 2020) - Mikaiel, Samantha; Simonelli, James; Li, Xinzhou; Lee, Yu‐Hsiu; Lee, Yong Seok; Sung, Kyunghyun; Lu, David S.; Tsao, Tsu‐Chin; Wu, Holden H.
Abstract: Background: Magnetic resonance imaging (MRI) has unique advantages for guiding interventions, but the narrow space is a major challenge. This study evaluates the feasibility of a remote‐controlled hydrostatic actuator system for MRI‐guided targeted needle placement. Methods: The effects of the hydrostatic actuator system on MR image quality were evaluated. Using a reference step‐and‐shoot method (SS) and the proposed actuator‐assisted method (AA), two operators performed MRI‐guided needle placement in targets (n = 12) in a motion phantom. Results: The hydrostatic actuator system exhibited negligible impact on MR image quality. In dynamic targets, AA was significantly more accurate and precise than SS, with mean ± SD needle‐to‐target error of 1.8 ± 1.0 mm (operator 1) and 1.3 ± 0.5 mm (operator 2). AA reduced the insertion time by 50% to 80% and total procedure time by 25%, compared to SS. Conclusions: The proposed hydrostatic actuator system may improve accuracy and reduce procedure time for MRI‐guided targeted needle placement during motion.